2001
DOI: 10.1096/fj.01-0280fje
|View full text |Cite
|
Sign up to set email alerts
|

Human inhibitor of apoptosis protein (IAP)survivinparticipates in regulation of chromosome segregation and mitotic exit

Abstract: A signaling cascade termed the "spindle checkpoint" monitors interactions between the kinetochores of chromosomes and spindle microtubules to prevent precocious separation of sister chromatids. We have investigated the role of human inhibitor of apoptosis protein (IAP) surviving in regulation of cell division. We demonstrate that HeLa and PtK1 cells transfected or microinjected with surviving anti-sense oligonucleotides produce significantly more polyploid and micronucleated progeny cells and show abortive mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Although survivin has been identified as an apoptosis inhibitor, it also plays a role in cell division. [55][56][57] One study demonstrated that the deletion of the survivin gene resulted in the absence of mitotic spindle, suggesting that survivin regulates chromosome segregation and cytokinesis. 58 In another study, an anti-survivin antibody application caused the premature separation of sister chromatids and the dysregulation of spindle-checkpoint activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although survivin has been identified as an apoptosis inhibitor, it also plays a role in cell division. [55][56][57] One study demonstrated that the deletion of the survivin gene resulted in the absence of mitotic spindle, suggesting that survivin regulates chromosome segregation and cytokinesis. 58 In another study, an anti-survivin antibody application caused the premature separation of sister chromatids and the dysregulation of spindle-checkpoint activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clonogenic survival of cells from each line was reduced by 65-86% (Fig 1c, Table 1). By using antisense oligonucleotides, 8,[10][11][12][34][35][36] ribozymes, 9,13,37 and siRNA (in a colon cancer cell line) 23 to knock down expression of survivin mRNA and protein, other investigators have observed a remarkable reduction in survivin mRNA that ranged from 70 to 90% and a reduction in survivin protein that ranged from 60 to 90%. The study conducted by Williams et al 23 has described the application of survivin-specific siRNA, which differs from the construct applied in our study, resulting in a reduction of survivin protein in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,12,23,25,26 However, the fate of these polyploid cells is not completely known. Chen and co-workers suggested that many of the polyploid cells undergo apoptosis; however, we and others 12,13 did not observe a large number of these cells undergoing apoptosis. Interestingly, in the clonogenic survival assay, polyploid cells were alive after 10-14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This finding is in accordance with results of survivin knockdown experiments in other cancer cell lines. 5,[16][17][18][19][20] Furthermore, survivin overexpression was associated with radioresistance in tumor cell lines. [21][22][23][24][25][26] The knockdown of survivin by ribozymes resulted in an increase of sensitivity of mt-p53 melanoma cells to irradiation.…”
Section: Introductionmentioning
confidence: 99%